Encyclopedia of tidepools and rocky shores - Denny, Mark W., 1951-; Gaines, Steven D. (Steven Dean), 1955- (Encyclopedias of the natural world, 2007)
Tidepools and rocky shores are among the most physically stressful environments on earth. When the tide is high, waves can sweep over plants and animals at velocities as high as 60 miles per hour, while at low tide, the same organisms dry up and bake in the sun. Yet despite this seeming inhospitality, tidepools and rocky shores are exceptionally complex and biologically diverse. This comprehensive encyclopedia is an authoritative, one-stop reference for everyone interested in the biology and ecology of this fascinating and uniquely accessible environment. Conveniently arranged alphabetically.